MANAGEMENT OF A CARAPACE FRACTURE IN A SIX-BANDED ARMADILLO (EUPHRACTUS SEXCINCTUS) - Rossetti, Diogo Pascoal [UNESP]; Rahal, Sheila Canevese [UNESP]; Vulcano, Luiz Carlos [UNESP]; Shigue, Daniela Akemi [UNESP]; Teixeira, Carlos Roberto [UNESP] (Amer Assoc Zoo Veterinarians, 2014)
An adult female free-ranging six-banded armadillo (Euphractus sexcinctus) was presented with an inverted L-shaped fracture of the left pectoral carapace. The fracture was stabilized with the use of three simple interrupted interfragmentary sutures of 2-0 nylon. After 7 days, wound dehiscence occurred, so sutures were replaced and the wound treated topically with castor bean oil cream. Healing of the fracture was observed after 14 days of this treatment.
Keywords: Armadillo; carapace; fracture; healing; Xenarthra